Narasi Al-Tsawab (الثواب) Dalam Al Quran Prespektif Linguistik Behaviourisme - Tri Tami Gunarti; Mubarok Ahmadi (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
This research contributes to explaining the contextualization of meaning in the Qur'an so that Muslims do not misunderstand the textual understanding and even understanding that is far from the truth. This study uses the theory of linguistic behaviorism pioneered by Bloomfield, this paper can also add to the treasures of knowledge related to the linguistic meaning of the Qur'an, especially with regard to the description of the reward in the Qur'an which was very attractive to Arab society at that time, thus many of them converted to Islam. After the author conducted an analysis of the Qur'anic verses that describe the reward with all its pleasures, the author found three main stimuli related to the condition of Arab society so that it gave rise to linguistic responses in the form of a reward description, namely: the socio-cultural situation of the community, portraits of royal life, and Arab geography.